Zeolite nano biological feed compound and preparation method thereof

By preparing zeolite nano-biofeed complexes and using raw materials such as zeolite and lactic acid bacteria dry powder, the problems of low digestibility and stability of biofeed were solved, and the efficiency of intestinal nutrient absorption was improved and environmental pollution was reduced.

CN120660796AInactive Publication Date: 2025-09-19BEIJING PANBAO BIOTECHNOLOGY GRP CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510759386.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-09
Publication Date
2025-09-19
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The digestibility of existing biofeeds and the stability of zeolite nano-biofeed complexes are low, and the degree of environmental pollution caused by aquaculture waste is high.

Method used

Zeolite, lactic acid bacteria powder, amylase products, cellulose, chitosan and citrus pectin are used as raw materials. Zeolite nano-biofeed complex is prepared through the steps of crushing, compounding, coating and testing to achieve nano-precision preparation and functional improvement.

Benefits of technology

It improves the absorption efficiency of nutrients in the animal intestine, reduces intestinal diseases and environmental pollution, enhances the intestinal barrier function, and improves the air quality of the breeding environment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120660796A_ABST
    Figure CN120660796A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of microbial animal feed, in particular to a zeolite nano biological feed compound and a preparation method thereof, and the zeolite nano biological feed compound is prepared from the following raw materials: zeolite, lactic acid bacteria dry powder, an amylase product, cellulose, chitosan and citrus pectin; the preparation method comprises the following steps: S1, carrying out crushing treatment on zeolite, and carrying out real-time crushing monitoring on the crushing treatment to obtain nano zeolite; s2, preparing the lactic acid bacteria dry powder and the amylase product to obtain the lactic acid bacteria dry powder and the amylase product; s3, composite treatment is conducted, and composite particles are obtained; s4, carrying out coating treatment, and carrying out real-time coating monitoring on the coating treatment to obtain target coated particles; and S5, carrying out safety detection. According to the invention, the digestibility of the biological feed and the stability and effectiveness of the zeolite nano biological feed compound are improved, and meanwhile, the pollution degree of breeding wastes to the environment is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of microbial animal feed, in particular to a zeolite nano-biological feed complex and a preparation method thereof. Background Art

[0002] With increasing concerns about food safety, environmental protection, and animal welfare, the market demand for biofeed compounds is growing. Modern animal husbandry is moving towards antibiotic-free, low-drug residue, and sustainable development. As a new type of feed additive, biofeed compounds combine the advanced nature of biotechnology with the nutritional properties of traditional feeds and are gradually becoming a key component of modern animal husbandry. With the continuous deepening of relevant research and technological advancements, the potential of biofeed compounds in improving animal production performance, promoting animal health, and protecting the environment will be further realized. Zeolite nanocomposites are expected to be widely used in poultry, livestock, and aquaculture. They can not only improve animal growth rate and health, but also enhance feed nutrient utilization, reduce the use of antibiotics and other chemicals, and promote the development of green and sustainable feed and animal husbandry.

[0003] Chinese Patent Publication No.: CN118177288A discloses the preparation and application of a novel feed additive of a bioactive peptide complex. The novel feed additive of the bioactive peptide complex is specifically composed of a bioactive peptide as the main ingredient and a composite of auxiliary materials, wherein the main ingredient bioactive peptide is a chemically synthesized peptide, auxiliary material 1 is a peptide mixture with a molecular weight of less than 2000Da obtained by enzymatic hydrolysis of marine microalgae, and dressing 2 is stone powder passed through a 20-80 mesh sieve. The main ingredient and auxiliary materials are composed in a certain ratio. The novel feed additive of the complex is a nutritional supplement for animals, used to protect the intestines and prevent intestinal inflammation. However, this invention is only used to protect the intestines and prevent intestinal inflammation, and it is difficult to improve the digestibility of biological feed and the stability and effectiveness of zeolite nano-biological feed complexes. Summary of the Invention

[0004] To this end, the present invention provides a zeolite nano-biofeed composite and a preparation method thereof, which are used to overcome the problems in the prior art of low digestibility of biofeed and low stability and effectiveness of the zeolite nano-biofeed composite, as well as high environmental pollution caused by aquaculture waste.

[0005] To achieve the above-mentioned object, the present invention provides a zeolite nano-bio-feed composite, wherein the raw materials for preparing the zeolite nano-bio-feed composite include: zeolite, lactic acid bacteria dry powder, amylase product, cellulose, chitosan and citrus pectin, wherein:

[0006] The mass of the zeolite is M1, and M1 is set as the first preset mass, M1=70 parts;

[0007] The mass of the lactic acid bacteria dry powder is M2, and M2 is set as the second preset mass, M2=10 parts;

[0008] The mass of the amylase product is M3, and M3 is set as the third preset mass, M3=10 parts;

[0009] The mass of the cellulose is M4, and M4 is set to be the fourth preset mass, M4=10 parts;

[0010] The mass fraction of the chitosan is M5, and M5 is set as the fifth preset mass fraction, M5=2 parts;

[0011] The mass fraction of the citrus pectin is M6, and M6 is set as the sixth preset mass fraction, M6=3 parts.

[0012] On the other hand, the present invention also provides a method for preparing a zeolite nano-biofeed composite, the preparation method comprising:

[0013] Step S1, crushing the zeolite and monitoring the crushing process in real time to obtain nano zeolite;

[0014] Step S2, preparing lactic acid bacteria dry powder and amylase product to obtain lactic acid bacteria dry powder and amylase product;

[0015] Step S3, compounding the nano-zeolite, the lactic acid bacteria powder, the amylase product and the cellulose to obtain composite particles;

[0016] Step S4, coating the composite particles, chitosan, and citrus pectin, and monitoring the coating process in real time to obtain target coated particles;

[0017] Step S5: Perform safety testing on the target coated particles to obtain zeolite nano-biofeed complex.

[0018] Furthermore, in step S1, when the zeolite is crushed, the specific surface area of ​​the zeolite is measured to obtain the specific surface area S of the zeolite, and the specific surface area S of the zeolite is compared with the preset specific surface area S0. The compliance of the specific surface area of ​​the zeolite is judged according to the comparison result, and the zeolite is output according to the judgment result, wherein:

[0019] When S≥S0, the zeolite specific surface area is determined to meet the standard, and the zeolite is output as a zeolite with a standard specific surface area, and the preset particle size d0 is calculated and set to d0=6 / (S×ρ), where ρ is the zeolite density;

[0020] When S<S0, it is determined that the specific surface area of ​​the zeolite does not meet the standard, and the zeolite is output as a zeolite with a specific surface area that does not meet the standard;

[0021] In the step S1, when the zeolite is crushed, the zeolite with a qualified specific surface area is added to a cleaner for cleaning to obtain a cleaned zeolite, and the cleaned zeolite is added to a crusher for preliminary crushing to a first particle size to obtain a first zeolite, and the first zeolite is added to a planetary ball mill for ball milling to obtain a ball-milled zeolite, wherein the first particle size is set to D1, the grinding medium of the planetary ball mill is Yj, the ball-to-material ratio of the ball milling is Q, the ball milling speed of the planetary ball mill is Vq, 100 mesh ≤ D1 ≤ 200 mesh, Yj is an agate ball, Q = 5:1, 200 r / min ≤ Vq ≤ 600 r / min;

[0022] When the zeolite is crushed in step S1, the actual particle size d of the ball-milled zeolite is also obtained, and the actual particle size d of the ball-milled zeolite is compared with the preset particle size d0. According to the comparison result, whether the actual particle size d of the ball-milled zeolite meets the standard is judged, and the ball-milled zeolite is output according to the judgment result, wherein:

[0023] When d≤d0, it is determined that the actual particle size d of the ball-milled zeolite meets the standard, and the ball-milled zeolite is output as nano zeolite;

[0024] When d>d0, it is determined that the actual particle size d of the ball-milled zeolite does not meet the standard, and the ball-milled zeolite is added back into the planetary ball mill for additional ball milling until the actual particle size d of the ball-milled zeolite meets the standard.

[0025] Furthermore, when the step S1 performs real-time crushing monitoring on the crushing process, the silicon-aluminum ratio of the zeolite with a non-standard specific surface area is detected by X-ray fluorescence spectroscopy to obtain the silicon-aluminum ratio G of the zeolite with a non-standard specific surface area, and the silicon-aluminum ratio G of the zeolite with a non-standard specific surface area is compared with the preset silicon-aluminum ratio G0 of the zeolite. According to the comparison result, the compliance of the silicon-aluminum ratio of the zeolite with a non-standard specific surface area is judged, and the zeolite with a non-standard specific surface area is optimized according to the judgment result, wherein:

[0026] When G≥G0, the silicon-aluminum ratio of the zeolite with a specific surface area that does not meet the standard is determined to meet the standard, and the optimization treatment of the zeolite with a specific surface area that does not meet the standard is to recycle the zeolite with a specific surface area that does not meet the standard;

[0027] When G<G0, it is determined that the silicon-to-aluminum ratio of the zeolite whose specific surface area does not meet the standard does not meet the standard. The optimization treatment method for the zeolite whose specific surface area does not meet the standard is to steam the zeolite whose specific surface area does not meet the standard to obtain steam zeolite, and judge whether the specific surface area of ​​the steam zeolite meets the standard.

[0028] Furthermore, when the step S1 performs real-time crushing monitoring on the crushing process, the non-framework aluminum content T of the zeolite whose specific surface area does not meet the standard is also obtained, and the non-framework aluminum content T of the zeolite whose specific surface area does not meet the standard is compared with the preset non-framework aluminum content T0. The effectiveness of the silicon-aluminum ratio G of the zeolite whose specific surface area does not meet the standard is judged according to the comparison result, and the judgment result of the compliance of the silicon-aluminum ratio of the zeolite whose specific surface area does not meet the standard is adjusted according to the judgment result, wherein:

[0029] When T≤T0, the effective case of the silicon-aluminum ratio G of the zeolite with a specific surface area that does not meet the standard is determined to be effective, and the judgment result of the silicon-aluminum ratio of the zeolite with a specific surface area that does not meet the standard is not adjusted;

[0030] When T>T0, the effective situation of judging the silicon-aluminum ratio G of the zeolite whose specific surface area does not meet the standard is invalid, and the judgment result of whether the silicon-aluminum ratio of the zeolite whose specific surface area does not meet the standard meets the standard is adjusted to judging that the silicon-aluminum ratio of the zeolite whose specific surface area does not meet the standard meets the standard is not up to standard.

[0031] Furthermore, in step S2, when preparing the lactic acid bacteria dry powder, a sample strain is collected from the animal intestinal environment, and a target strain is separated from the sample strain by a plate streaking method, the target strain is subjected to physiological and biochemical identification and molecular biological identification to obtain lactic acid bacteria, the lactic acid bacteria is added to an MRS medium for expansion culture to obtain a lactic acid bacteria fermentation broth, and the lactic acid bacteria cells in the lactic acid bacteria fermentation broth are separated by a cell centrifugation method to obtain lactic acid bacteria cells, the lactic acid bacteria cells are concentrated to obtain concentrated cells, and the concentrated cells are dried using a freeze-drying method to obtain lactic acid bacteria dry powder, and the temperature of the expansion culture is set to A, 30°C ≤ A ≤ 42°C, and the oxygen condition is anaerobic condition;

[0032] When preparing the amylase product in step S2, Bacillus and Aspergillus are screened by an enzyme activity assay, and Bacillus and Aspergillus with enzyme activities that meet preset enzyme activities are used as production strains, and the production strains are inoculated into a liquid culture medium for fermentation culture to obtain an enzyme fermentation liquid, and the enzyme cells and impurities in the enzyme fermentation liquid are removed by enzyme centrifugation to obtain a crude enzyme liquid, and the crude enzyme liquid is purified to obtain the amylase product, and the fermentation culture temperature is set to Af, 30°C≤Af≤37°C, and the fermentation culture pH value is set to P, 6≤P≤7.

[0033] Furthermore, in step S3, when performing the composite treatment, the nano zeolite is added to deionized water to obtain a deionized liquid, and the deionized liquid is placed in a magnetic stirrer for magnetic stirring to obtain a suspension, and the suspension is placed in a high-speed stirrer for high-speed stirring to obtain a zeolite dispersion, and the lactic acid bacteria dry powder, amylase product and cellulose are added to the zeolite dispersion, and composite stirring is performed using a high-speed stirrer to obtain a composite solution, and the composite solution is placed in a centrifuge for centrifugal treatment, and the supernatant is removed to obtain a composite precipitate, the composite precipitate is washed, and the centrifugal treatment is repeated until the washing treatment is repeated 3 times to obtain a zeolite biocomposite, and the zeolite biocomposite is vacuum dried to obtain composite particles, wherein:

[0034] The speed of magnetic stirring is Vc, the time of magnetic stirring is Bc, 200r / min≤Vc≤500r / min, 10min≤Bc≤15min;

[0035] The speed of high-speed stirring is Vg, the time of high-speed stirring is Bg, 1000r / min≤Vg≤5000r / min, 1h≤Bg≤2h;

[0036] The speed of compound stirring is Vf, the time of compound stirring is Bf, 800r / min≤Vf≤3000r / min, 2h≤Bf≤4h;

[0037] The speed of centrifugal treatment is Vx, the time of centrifugal treatment is Bx, 3000r / min≤Vf≤8000r / min, 10min≤Bf≤15min;

[0038] The vacuum degree of the vacuum drying process is Cz, the temperature of the vacuum drying process is Az, -0.08MPa≤Bf≤-0.1MPa, 30℃≤Az≤60℃.

[0039] Furthermore, in step S4, when performing the coating treatment, chitosan of a preset dissolution mass is added to an acetic acid solution of a preset dissolution volume for dissolution to obtain a chitosan solvent of a target concentration, and the composite particles are added to the chitosan solvent of the target concentration to obtain a chitosan composite agent, and genipin of a preset cross-linking mass is added to the chitosan composite agent for cross-linking treatment to obtain a cross-linked product, and the cross-linked product is centrifuged and washed to obtain a chitosan coating, and the concentration of the acetic acid solution of the preset dissolution volume is set to Ey, Ey=1%, the target concentration is Em, Em=2%, the cross-linking treatment temperature is Aj l, Aj l=50°C, and the cross-linking treatment time is Bjl, Bjl=1h;

[0040] During the coating treatment in step S4, citrus pectin of a preset pectin mass is added to a preset second dissolution volume of deionized water to obtain a citrus pectin solution of a second target concentration, and the pH value of the citrus pectin solution of the second target concentration is adjusted to 4.5 to obtain a target citrus pectin solution, and calcium chloride of a preset induced mass is added to a preset induced volume of deionized water to obtain a calcium chloride solution of a target induced concentration, and the calcium chloride solution of the target induced concentration is added to the target citrus pectin solution to induce gelation to obtain a pectin solvent, and the chitosan coating is immersed in the pectin solvent and immersed and stirred to obtain a mixture, and the mixture is mixed and centrifuged to obtain composite coated particles, and the second target concentration is set to Ed, Ed=3%, the target induction concentration is set to Eyd, Eyd=5%, and the immersion and stirring time is set to Bqr, Bqr=30min.

[0041] Furthermore, in step S4, when the coating treatment is performed in real time, the pH value of the chitosan dissolution process is obtained in real time to obtain a real-time dissolution pH value Prj, and the real-time dissolution pH value Prj is compared with the preset dissolution pH value P0. The effectiveness of the chitosan dissolution is judged according to the comparison result, and the chitosan dissolution process is corrected according to the judgment result, wherein:

[0042] When Prj>P0, the chitosan dissolution is determined to be invalid. The chitosan dissolution process is corrected by adding a first correction volume of acetic acid solution to the preset dissolution volume of acetic acid solution. The preset dissolution volume is set to F1, the first correction volume is set to Fj1, and the concentration of the first correction volume of acetic acid solution is set to Ey1, Ey1=1%, Fj1=5%×F1;

[0043] When Prj = P0, the chitosan dissolution is determined to be effective, and the chitosan dissolution process is not corrected;

[0044] When Prj<P0, the chitosan dissolution is determined to be invalid. The chitosan dissolution process is corrected by adding a second correction volume of sodium hydroxide solution to the preset dissolution volume of acetic acid solution. The preset dissolution volume is set to F1, the second correction volume is set to Fj2, and the concentration of the second correction volume of sodium hydroxide solution is Eq1, Eq1=1%, Fj2=5%×F1;

[0045] When the coating process is monitored in real time in step S4, the film thickness of the composite coated particles is obtained to obtain the composite coated particle film thickness H, and the composite coated particle film thickness H is compared with the preset composite coated particle film thickness H0. The effectiveness of the coating process is judged based on the comparison result, and the coating process is optimized in real time based on the judgment result, wherein:

[0046] When H>H0, the coating treatment is determined to be invalid, and the real-time optimization treatment method of the coating treatment process is to soak the composite coated particles in a weakly acidic aqueous solution for 5 minutes to obtain soaked particles, and optimize the drying treatment of the soaked particles to obtain real-time optimized particles, and obtain the film thickness of the real-time optimized particles. When the film thickness of the real-time optimized particles is reduced to the preset composite coated particle film thickness H0, the real-time optimized particles are output as target coated particles;

[0047] When H=H0, the coating treatment is judged to be effective, and the coating treatment process is not optimized in real time;

[0048] When H<H0, the effectiveness of the coating treatment is determined to be invalid, and the real-time optimization method of the coating treatment process is to perform real-time optimization on the preset dissolution mass and the preset pectin mass, and set the preset dissolution mass after real-time optimization to J1`, and the preset pectin mass after real-time optimization to J2`, the preset dissolution mass is J1, the preset pectin mass is J2, J1`=J1×H0 / H, J2`=J2×H0 / H, and repeat the coating treatment process according to the preset dissolution mass J1` after real-time optimization and the preset pectin mass J2` after real-time optimization.

[0049] Furthermore, in step S5, when the target coated particles are subjected to safety testing, the residual amount of genipin in the target coated particles is detected by HPLC to obtain a residual amount N of genipin, and the residual amount N of genipin is compared with a preset residual amount N0 of genipin. The safety compliance of the target coated particles is judged according to the comparison results, and the target coated particles are output according to the judgment results, wherein;

[0050] When N≥N0, the target coated particles are judged to have failed to meet the safety standards. The target coated particles are output by using an adsorption material to adsorb the target coated particles to obtain treated particles, and safety testing is performed on the treated particles until the safety standards of the treated particles are met.

[0051] When N<N0, the safety compliance of the target coated particles is determined to be met, and the output method of the target coated particles is to pre-freeze the target coating at -40℃ for 4h to obtain a pre-frozen coating, and the pre-frozen coating is post-processed and vacuum-dried to obtain a zeolite nano-biofeed complex. The vacuum degree of the post-processing vacuum drying is set to Chc, the temperature of the post-processing vacuum drying is set to Ahc, and the time of the post-processing vacuum drying is set to Bhc, -0.06MPa≤Chc≤-0.08MPa, Ahc=-50℃, and Bhc=24h.

[0052] Compared with the prior art, the present invention has the following beneficial effects: the zeolite nano-biofeed compound introduces zeolite to absorb harmful substances in the animal intestine, reducing the damage of harmful substances to the animal intestinal mucosa; at the same time, the zeolite nano-biofeed compound introduces chitosan and citrus pectin to form a sticky protective film in the intestine, thereby reducing the irritation of feed and harmful substances to the intestine, enhancing the intestinal barrier function, and thus improving the absorption efficiency of nutrients; the zeolite nano-biofeed compound also introduces lactic acid bacteria dry powder as beneficial bacteria, which can colonize in the animal intestine, thereby inhibiting the reproduction of harmful bacteria and regulating the balance of intestinal flora. The occurrence of intestinal diseases is reduced, and the starch in the feed is broken down into small molecules by introducing amylase products. At the same time, the partial degradation of the introduced cellulose can soften the feed structure, further improve the palatability, and increase the animal's feed intake. The zeolite nano-biofeed complex introduces zeolite, lactic acid bacteria dry powder, amylase products, cellulose, chitosan and citrus pectin to improve the feed digestibility, enable animals to absorb nutrients more fully, reduce the excretion of nitrogen, phosphorus and other substances with feces, and reduce the pollution of aquaculture waste to the environment. At the same time, the adsorption of zeolite can also reduce the generation of harmful gases in the intestine, thereby improving the air quality of the aquaculture environment.

[0053] In particular, the preparation method performs real-time monitoring of specific surface area, graded crushing and closed-loop control of particle size through step S1 to achieve precise nano-scale preparation of zeolite, laying a core foundation for the functionality, stability and production economy of zeolite nano-biofeed complex. The preparation method also introduces a dual detection mechanism of silicon-aluminum ratio and non-framework aluminum content through step S1, constructs a closed-loop control system of "structure-performance-optimization", so as to solve the structural defects in the preparation of nano-zeolite, and improves the intelligence level of the preparation process through closed-loop control, thereby improving the production efficiency of zeolite nano-biofeed complex. The preparation method realizes the activity retention and performance optimization of functional microorganisms and enzyme preparations through step S2, thereby forming a virtuous cycle of "enzymolysis-fermentation", so as to improve the effectiveness and stability of zeolite nano-biofeed complex. The preparation method performs multi-stage stirring, centrifugation and drying processes through step S3 to achieve efficient dispersion of each component. The preparation method is tightly combined with the active ingredient, so that the prepared composite particles have the characteristics of uniform component distribution, high purity and strong activity, so as to improve the nutritional value and digestibility of the zeolite nano-biofeed composite. The preparation method performs a double-layer coating process of "chitosan cross-linking-pectin gelation" in step S4 to improve the activity retention of functional ingredients during storage, processing and digestion, thereby further improving the nutritional value and digestibility of the zeolite nano-biofeed composite. The preparation method also performs intelligent monitoring of "pH dynamic correction-film thickness closed-loop control" in step S4 to achieve precise regulation of the coating process, thereby improving the stability and effectiveness of the zeolite nano-biofeed composite. The preparation method performs a process design of "detection-adsorption-re-detection-drying" in step S5 to achieve quality assurance of the zeolite nano-biofeed composite, thereby further improving the stability and effectiveness of the zeolite nano-biofeed composite. BRIEF DESCRIPTION OF THE DRAWINGS

[0054] Figure 1 Schematic diagram of the process for preparing the zeolite nano-biofeed complex of this embodiment. DETAILED DESCRIPTION

[0055] In order to make the objects and advantages of the present invention more clearly understood, the present invention is further described below in conjunction with embodiments; it should be understood that the specific embodiments described herein are merely used to explain the present invention and are not intended to limit the present invention.

[0056] The preferred embodiments of the present invention are described below with reference to the accompanying drawings. It should be understood by those skilled in the art that these embodiments are only used to explain the technical principles of the present invention and are not intended to limit the scope of protection of the present invention.

[0057] It should be noted that, in the description of the present invention, terms such as "up", "down", "left", "right", "inside", and "outside" indicating directions or positional relationships are based on the directions or positional relationships shown in the accompanying drawings. This is only for the convenience of description and does not indicate or imply that the device or element must have a specific orientation, be constructed and operated in a specific orientation. Therefore, it cannot be understood as a limitation on the present invention.

[0058] Furthermore, it should be noted that, in the description of the present invention, unless otherwise expressly specified or limited, the terms "mounted," "connected," and "connected" should be understood in a broad sense. For example, they may refer to fixed connections, detachable connections, or integral connections; mechanical connections or electrical connections; direct connections or indirect connections through an intermediate medium; and internal communication between two components. Those skilled in the art will understand the specific meanings of the above terms in the present invention based on specific circumstances.

[0059] A zeolite nano-biofeed compound, wherein the raw materials for preparing the zeolite nano-biofeed compound include: zeolite, lactic acid bacteria dry powder, amylase product, cellulose, chitosan and citrus pectin, wherein:

[0060] The mass of the zeolite is M1, and M1 is set as the first preset mass, M1=70 parts;

[0061] The mass of the lactic acid bacteria dry powder is M2, and M2 is set as the second preset mass, M2=10 parts;

[0062] The mass of the amylase product is M3, and M3 is set as the third preset mass, M3=10 parts;

[0063] The mass of the cellulose is M4, and M4 is set to be the fourth preset mass, M4=10 parts;

[0064] The mass fraction of the chitosan is M5, and M5 is set as the fifth preset mass fraction, M5=2 parts;

[0065] The mass fraction of the citrus pectin is M6, and M6 is set as the sixth preset mass fraction, M6=3 parts.

[0066] Specifically, the zeolite nano-biofeed complex introduces zeolite to absorb harmful substances in the animal intestine and reduce the damage of harmful substances to the animal intestinal mucosa. At the same time, the zeolite nano-biofeed complex introduces chitosan and citrus pectin to form a sticky protective film in the intestine to reduce the stimulation of feed and harmful substances to the intestine, enhance the intestinal barrier function, and thus improve the absorption efficiency of nutrients. The zeolite nano-biofeed complex also introduces lactic acid bacteria dry powder as beneficial bacteria, which can colonize in the animal intestine, thereby inhibiting the reproduction of harmful bacteria, regulating the balance of intestinal flora, and reducing the occurrence of intestinal diseases. The invention relates to a nano-bio-feed composite material, which is a kind of feed material, and decomposes the starch in the feed into small molecules by introducing amylase products. At the same time, the partial degradation of the introduced cellulose can soften the feed structure, further improve the palatability, and increase the animal's feed intake. The zeolite nano-bio-feed composite material introduces zeolite, lactic acid bacteria dry powder, amylase products, cellulose, chitosan and citrus pectin to improve the feed digestibility, enable the animal to absorb nutrients more fully, reduce the excretion of nitrogen, phosphorus and other substances with feces, and reduce the pollution of aquaculture waste to the environment. At the same time, the adsorption of zeolite can also reduce the generation of harmful gases in the intestine, thereby improving the air quality of the aquaculture environment.

[0067] See also Figure 1 , which is a schematic flow chart of the preparation method of the zeolite nano-biofeed compound of this embodiment, the preparation method comprises:

[0068] Step S1, crushing the zeolite and monitoring the crushing process in real time to obtain nano zeolite;

[0069] Step S2, preparing lactic acid bacteria dry powder and amylase product to obtain lactic acid bacteria dry powder and amylase product;

[0070] Step S3, compounding the nano-zeolite, the lactic acid bacteria powder, the amylase product and the cellulose to obtain composite particles;

[0071] Step S4, coating the composite particles, chitosan, and citrus pectin, and monitoring the coating process in real time to obtain target coated particles;

[0072] Step S5: Perform safety testing on the target coated particles to obtain zeolite nano-biofeed complex.

[0073] Specifically, the preparation method is applied to the preparation process of zeolite nano-biofeed complex. The preparation method crushes, prepares, compounds, coats, detects and monitors the raw materials for the preparation of zeolite nano-biofeed complex in real time to achieve a standardized and intelligent production process, thereby improving the effectiveness and stability of the zeolite nano-biofeed complex. In particular, the preparation method performs real-time monitoring of specific surface area, graded crushing and closed-loop control of particle size through step S1 to achieve nano-precision preparation of zeolite, laying a core foundation for the functionality, stability and production economy of zeolite nano-biofeed complex. The preparation method also introduces a dual detection mechanism of silicon-aluminum ratio and non-framework aluminum content through step S1, constructs a "structure-performance-optimization" closed-loop control system, so as to solve the structural defects in the preparation of nano-zeolite, and improves the intelligence level of the preparation process through closed-loop control, thereby improving the production efficiency of zeolite nano-biofeed complex. The preparation method realizes the activity retention and performance optimization of functional microorganisms and enzyme preparations through step S2, thereby forming a virtuous cycle of "enzymatic hydrolysis-fermentation", so as to To improve the effectiveness and stability of the zeolite nano-biofeed complex, the preparation method performs a multi-stage stirring, centrifugation, and drying process in step S3 to achieve efficient dispersion and tight binding of the components, so that the prepared complex particles have the characteristics of uniform component distribution, high purity, and strong activity, thereby improving the nutritional value and digestibility of the zeolite nano-biofeed complex. The preparation method performs a double-layer coating process of "chitosan cross-linking-pectin gelation" in step S4 to enhance the activity retention of functional components during storage, processing, and digestion, thereby further improving the nutritional value and digestibility of the zeolite nano-biofeed complex. The preparation method also performs intelligent monitoring of "pH dynamic correction-film thickness closed-loop control" in step S4 to achieve precise regulation of the coating process, thereby improving the stability and effectiveness of the zeolite nano-biofeed complex. The preparation method performs a "detection-adsorption-redetection-drying" process design in step S5 to achieve quality assurance of the zeolite nano-biofeed complex, thereby further improving the stability and effectiveness of the zeolite nano-biofeed complex.

[0074] Specifically, when the zeolite is crushed in step S1, the specific surface area of ​​the zeolite is measured to obtain the specific surface area S of the zeolite, and the specific surface area S of the zeolite is compared with the preset specific surface area S0. The compliance of the specific surface area of ​​the zeolite is judged according to the comparison result, and the zeolite is output according to the judgment result, wherein:

[0075] When S≥S0, the zeolite specific surface area is determined to meet the standard, and the zeolite is output as a zeolite with a standard specific surface area, and the preset particle size d0 is calculated and set to d0=6 / (S×ρ), where ρ is the zeolite density;

[0076] When S<S0, it is determined that the specific surface area of ​​the zeolite does not meet the standard, and the zeolite is output as a zeolite with a specific surface area that does not meet the standard;

[0077] In the step S1, when the zeolite is crushed, the zeolite with a qualified specific surface area is added to a cleaner for cleaning to obtain a cleaned zeolite, and the cleaned zeolite is added to a crusher for preliminary crushing to a first particle size to obtain a first zeolite, and the first zeolite is added to a planetary ball mill for ball milling to obtain a ball-milled zeolite, wherein the first particle size is set to D1, the grinding medium of the planetary ball mill is Yj, the ball-to-material ratio of the ball milling is Q, the ball milling speed of the planetary ball mill is Vq, 100 mesh ≤ D1 ≤ 200 mesh, Yj is an agate ball, Q = 5:1, 200 r / min ≤ Vq ≤ 600 r / min;

[0078] When the zeolite is crushed in step S1, the actual particle size d of the ball-milled zeolite is also obtained, and the actual particle size d of the ball-milled zeolite is compared with the preset particle size d0. According to the comparison result, whether the actual particle size d of the ball-milled zeolite meets the standard is judged, and the ball-milled zeolite is output according to the judgment result, wherein:

[0079] When d≤d0, it is determined that the actual particle size d of the ball-milled zeolite meets the standard, and the ball-milled zeolite is output as nano zeolite;

[0080] When d>d0, it is determined that the actual particle size d of the ball-milled zeolite does not meet the standard, and the ball-milled zeolite is added back into the planetary ball mill for additional ball milling until the actual particle size d of the ball-milled zeolite meets the standard.

[0081] Specifically, the zeolite specific surface area refers to the surface area of ​​zeolite per unit mass, the preset specific surface area S0 refers to the preset minimum standard value of the zeolite specific surface area, for example, the preset specific surface area S0 = 500 m2 / g, the preset particle size d0 refers to the target size of the zeolite particles to be obtained, the zeolite density refers to the mass of zeolite per unit volume, in grams per cubic centimeter, the cleaner refers to a device for removing impurities and contaminants from the surface of zeolite, such as an ultrasonic cleaner and a steam jet cleaner, the crusher refers to a device for crushing zeolite to a specified particle size, such as a ball mill and a hammer crusher, and the planetary ball mill refers to a device for grinding materials by planetary motion. equipment, the first particle size refers to the particle size of the zeolite particles obtained after preliminary crushing, the grinding medium of the planetary ball mill refers to the material used to impact and grind the zeolite during the ball milling process, the ball-to-material ratio of the ball mill refers to the mass ratio of the grinding medium to the material during the ball milling process, the ball milling speed of the planetary ball mill refers to the rotation speed of the grinding medium of the planetary ball mill during operation, the agate ball refers to the ball milling medium made of agate material, and the actual particle size d refers to the actual particle size of the zeolite particles after ball milling. This embodiment does not limit the method for obtaining the actual particle size d of the ball-milled zeolite. For example, it can be set to obtain the actual particle size d of the ball-milled zeolite through a particle size analyzer.

[0082] Specifically, when the zeolite is crushed in step S1, real-time monitoring of specific surface area, graded crushing and closed-loop control of particle size are performed to achieve precise nano-scale preparation of zeolite, laying a core foundation for the functionality, stability and production economy of zeolite nano-biofeed complexes.

[0083] Specifically, when the pulverization process is performed in real time on the step S1, the silicon-aluminum ratio of the zeolite with a non-standard specific surface area is detected by X-ray fluorescence spectroscopy to obtain the silicon-aluminum ratio G of the zeolite with a non-standard specific surface area, and the silicon-aluminum ratio G of the zeolite with a non-standard specific surface area is compared with the preset silicon-aluminum ratio G0 of the zeolite. According to the comparison result, the compliance of the silicon-aluminum ratio of the zeolite with a non-standard specific surface area is judged, and the zeolite with a non-standard specific surface area is optimized according to the judgment result, wherein:

[0084] When G≥G0, the silicon-aluminum ratio of the zeolite with a specific surface area that does not meet the standard is determined to meet the standard, and the optimization treatment of the zeolite with a specific surface area that does not meet the standard is to recycle the zeolite with a specific surface area that does not meet the standard;

[0085] When G<G0, the silicon-to-aluminum ratio of the zeolite with a non-standard specific surface area is determined to be non-standard, and an optimization method for treating the zeolite with a non-standard specific surface area is to steam the zeolite with a non-standard specific surface area to obtain a steam zeolite, and determine whether the specific surface area of ​​the steam zeolite meets the standard;

[0086] When the step S1 performs real-time crushing monitoring on the crushing process, the non-framework aluminum content T of the zeolite with a non-standard specific surface area is also obtained, and the non-framework aluminum content T of the zeolite with a non-standard specific surface area is compared with a preset non-framework aluminum content T0. The effectiveness of the silicon-to-aluminum ratio G of the zeolite with a non-standard specific surface area is judged according to the comparison result, and the judgment result of the compliance of the silicon-to-aluminum ratio of the zeolite with a non-standard specific surface area is adjusted according to the judgment result, wherein:

[0087] When T≤T0, the effective case of the silicon-aluminum ratio G of the zeolite with a specific surface area that does not meet the standard is determined to be effective, and the judgment result of the silicon-aluminum ratio of the zeolite with a specific surface area that does not meet the standard is not adjusted;

[0088] When T>T0, the effective situation of judging the silicon-aluminum ratio G of the zeolite whose specific surface area does not meet the standard is invalid, and the judgment result of whether the silicon-aluminum ratio of the zeolite whose specific surface area does not meet the standard meets the standard is adjusted to judging that the silicon-aluminum ratio of the zeolite whose specific surface area does not meet the standard meets the standard is not up to standard.

[0089] Specifically, the X-ray fluorescence spectrometry refers to a method of performing qualitative and quantitative elemental analysis by irradiating a sample with X-rays and analyzing the fluorescent X-rays emitted by the sample. The silicon-aluminum ratio detection refers to the process of evaluating the structure and properties of the zeolite by measuring the content ratio of silicon to aluminum in the zeolite. The silicon-aluminum ratio G of the zeolite that does not meet the specific surface area standard refers to the result obtained after measuring the silicon-aluminum ratio of the zeolite that does not meet the preset specific surface area standard. The preset zeolite silicon-aluminum ratio G0 refers to the preset minimum standard value of the zeolite silicon-aluminum ratio, for example, the preset zeolite silicon-aluminum ratio G0=5. The recycling process refers to the recycling of the zeolite that does not meet the specific surface area standard. The process of recycling zeolite, such as mechanical grinding and pickling, the steam treatment refers to the process of applying steam to the zeolite whose specific surface area does not meet the standard, the non-framework aluminum content T of the zeolite whose specific surface area does not meet the standard refers to the content of aluminum elements in non-framework form in the zeolite, and the preset non-framework aluminum content T0 refers to the pre-set standard value of the zeolite non-framework aluminum content, for example, the preset non-framework aluminum content T0 = 5%. This embodiment does not limit the method of obtaining the non-framework aluminum content T of the zeolite whose specific surface area does not meet the standard, such as it can be set to obtain the non-framework aluminum content T of the zeolite whose specific surface area does not meet the standard through infrared spectroscopy.

[0090] Specifically, when the step S1 performs real-time pulverization monitoring on the pulverization process, a dual detection mechanism of silicon-aluminum ratio and non-framework aluminum content is introduced to construct a "structure-performance-optimization" closed-loop control system to solve the structural defects in the preparation of nano-zeolites, and improve the intelligence level of the preparation process through closed-loop control, thereby improving the production efficiency of zeolite nano-biofeed complexes.

[0091] Specifically, when preparing the lactic acid bacteria dry powder in step S2, a sample strain is collected from the animal intestinal environment, and a target strain is separated from the sample strain by a plate drawing method, the target strain is subjected to physiological and biochemical identification and molecular biological identification to obtain lactic acid bacteria, the lactic acid bacteria is added to an MRS medium for expansion culture to obtain a lactic acid bacteria fermentation broth, and the lactic acid bacteria cells in the lactic acid bacteria fermentation broth are separated by a cell centrifugation method to obtain lactic acid bacteria cells, the lactic acid bacteria cells are concentrated to obtain concentrated cells, and the concentrated cells are dried by a freeze-drying method to obtain lactic acid bacteria dry powder, and the temperature of the expansion culture is set to A, 30°C≤A≤42°C, and the oxygen condition is anaerobic condition;

[0092] When preparing the amylase product in step S2, Bacillus and Aspergillus are screened by an enzyme activity assay, and Bacillus and Aspergillus with enzyme activities that meet preset enzyme activities are used as production strains, and the production strains are inoculated into a liquid culture medium for fermentation culture to obtain an enzyme fermentation liquid, and the enzyme cells and impurities in the enzyme fermentation liquid are removed by enzyme centrifugation to obtain a crude enzyme liquid, and the crude enzyme liquid is purified to obtain the amylase product, and the fermentation culture temperature is set to Af, 30°C≤Af≤37°C, and the fermentation culture pH value is set to P, 6≤P≤7.

[0093] Specifically, the animal intestinal environment refers to the microbial community in the digestive tract of the animal and the ecological environment in which it is located. The sample strain refers to the microbial sample collected from the animal intestinal environment, such as bacteria, fungi and protozoa. The target strain refers to the lactic acid bacteria successfully separated and identified from the sample strain by the plate streaking method. The physiological and biochemical identification refers to the method of analyzing the characteristics of the target strain through physiological and biochemical tests to confirm its type and biological characteristics. The molecular biological identification refers to the method of identifying the target strain using molecular biological technology to determine its genetic information, taxonomic status and characteristics. The MRS medium refers to the selective medium for culturing lactic acid bacteria. The expanded culture It refers to the process of inoculating the separated lactic acid bacteria into a larger volume of culture medium under suitable culture conditions to increase the number of bacteria. The bacterial centrifugation method refers to the process of separating the bacteria in the lactic acid bacteria fermentation broth from the culture medium by centrifugation technology. The concentration treatment refers to the process of treating the lactic acid bacteria to reduce its volume and increase its concentration. This embodiment does not limit the specific method of concentrating the lactic acid bacteria. For example, it can be set to concentrate the lactic acid bacteria by ultrafiltration. The freeze-drying method refers to the process of converting the water in the liquid into solid ice by freezing and then removing the ice by vacuum sublimation. The temperature of the expanded culture refers to the temperature range set when culturing lactic acid bacteria. The oxygen condition Refers to the controlled state of oxygen, the anaerobic condition refers to fermentation in an oxygen-free environment, the enzyme activity assay refers to the process of determining the activity of an enzyme by experimental methods of substrate consumption and product generation, the Bacillus refers to bacteria that can form spores, the Aspergillus refers to fungi that can produce amylase, the enzyme activity refers to the amount of reaction catalyzed by the enzyme per unit time, the preset enzyme activity refers to a preset enzyme activity standard value, for example, the preset enzyme activity is 500U / g, the lactic acid bacteria refers to bacteria that can ferment lactose and produce lactic acid, the fermentation culture refers to the process of culturing microorganisms to promote their growth and the production of metabolites, and the enzyme centrifugation method refers to the removal of impurities and The process of removing cell debris to obtain a clean crude enzyme solution, the enzyme bacteria refer to microbial cells with enzyme activity produced during the fermentation process, the impurities refer to non-target substances produced during the fermentation process, such as cell residues and metabolic by-products, the purification treatment refers to a method of removing impurities in the crude enzyme solution by physical and chemical methods to obtain a high-purity amylase product, such as filtration, precipitation and chromatography, the fermentation culture temperature refers to the temperature range controlled during the fermentation process, and the fermentation culture pH value refers to the acidity and alkalinity controlled during the fermentation process. This embodiment does not limit the method of collecting sample strains from the animal intestinal environment, such as it can be set to use an invasive collection method to collect sample strains from the animal intestinal environment.

[0094] Specifically, when preparing the lactic acid bacteria dry powder and amylase product in step S2, the activity retention and performance optimization of functional microorganisms and enzyme preparations are achieved through the preparation process of "strain screening-directional cultivation-efficient separation", thereby forming a virtuous cycle of "enzymolysis-fermentation", so as to improve the effectiveness and stability of the zeolite nano-biofeed complex.

[0095] Specifically, in step S3, when performing the composite treatment, the nano zeolite is added to deionized water to obtain a deionized liquid, and the deionized liquid is placed in a magnetic stirrer for magnetic stirring to obtain a suspension, and the suspension is placed in a high-speed stirrer for high-speed stirring to obtain a zeolite dispersion, and the lactic acid bacteria dry powder, amylase product and cellulose are added to the zeolite dispersion, and a high-speed stirrer is used for composite stirring to obtain a complex solution, and the complex solution is placed in a centrifuge for centrifugal treatment, and the supernatant is removed to obtain a composite precipitate, the composite precipitate is washed, and the centrifugal treatment is repeated until the washing treatment is repeated 3 times to obtain a zeolite biocomposite, and the zeolite biocomposite is vacuum dried to obtain composite particles, wherein:

[0096] The speed of magnetic stirring is Vc, the time of magnetic stirring is Bc, 200r / min≤Vc≤500r / min, 10min≤Bc≤15min;

[0097] The speed of high-speed stirring is Vg, the time of high-speed stirring is Bg, 1000r / min≤Vg≤5000r / min, 1h≤Bg≤2h;

[0098] The speed of compound stirring is Vf, the time of compound stirring is Bf, 800r / min≤Vf≤3000r / min, 2h≤Bf≤4h;

[0099] The speed of centrifugal treatment is Vx, the time of centrifugal treatment is Bx, 3000r / min≤Vf≤8000r / min, 10min≤Bf≤15min;

[0100] The vacuum degree of the vacuum drying process is Cz, the temperature of the vacuum drying process is Az, -0.08MPa≤Bf≤-0.1MPa, 30℃≤Az≤60℃.

[0101] Specifically, the deionized water refers to water after the ionic impurities in the water have been removed through the deionization process, the magnetic stirrer refers to a device that uses magnetic force to drive stirring, the magnetic stirring refers to the process of rotating the stirring rod in the magnetic stirrer by magnetic force to achieve mixing and stirring of the liquid, the high-speed stirrer refers to a device that can stir the liquid at a high speed, the high-speed stirring refers to the liquid stirring process at a high speed in a high-speed stirrer, the composite stirring refers to the process of adding lactic acid bacteria powder, amylase products and cellulose to the liquid at the same time for mixing on the basis of high-speed stirring, the centrifuge refers to a device that generates centrifugal force by high-speed rotation, the centrifugal treatment refers to the process of precipitating heavier solid matter by rotating the centrifuge to separate the supernatant, the supernatant refers to the clear liquid located on the upper layer of the liquid after centrifugal treatment, and the washing treatment refers to the use of deionized water to remove the surface of the composite precipitate The process of removing impurities from the surface, the vacuum drying treatment refers to the process of drying the sample in a vacuum environment, the speed of the magnetic stirring refers to the rotation speed of the stirring rod when performing magnetic stirring, the time of the magnetic stirring refers to the time lasting during the magnetic stirring process, the speed of the high-speed stirring refers to the rotation speed of the stirrer when performing high-speed stirring, the time of the high-speed stirring refers to the time lasting during the high-speed stirring process, the speed of the composite stirring refers to the rotation speed of the stirrer when performing composite stirring, the time of the composite stirring refers to the time lasting during the composite stirring process, the speed of the centrifugal treatment refers to the rotation speed of the centrifuge when performing centrifugal treatment, the time of the centrifugal treatment refers to the time lasting during the centrifugal treatment, the vacuum degree of the vacuum drying treatment refers to the vacuum pressure set when performing vacuum drying, and the temperature of the vacuum drying treatment refers to the temperature range set when performing vacuum drying.

[0102] Specifically, during the compounding process in step S3, efficient dispersion and tight combination of the components are achieved through multi-stage stirring, centrifugation and drying processes, so that the prepared composite particles have the characteristics of uniform component distribution, high purity and strong activity, so as to improve the nutritional value and digestibility of the zeolite nano-biofeed composite.

[0103] Specifically, in step S4, when performing the coating treatment, chitosan of a preset dissolution mass is added to an acetic acid solution of a preset dissolution volume for dissolution to obtain a chitosan solvent of a target concentration, and the composite particles are added to the chitosan solvent of the target concentration to obtain a chitosan complex, and a preset cross-linking mass of genipin is added to the chitosan complex for cross-linking treatment to obtain a cross-linked product, and the cross-linked product is centrifuged and washed to obtain a chitosan coating, and the concentration of the acetic acid solution of the preset dissolution volume is set to Ey, Ey=1%, the target concentration is Em, Em=2%, the cross-linking treatment temperature is Aj l, Aj l=50°C, and the cross-linking treatment time is Bjl, Bjl=1h;

[0104] During the coating treatment in step S4, citrus pectin of a preset pectin mass is added to a preset second dissolution volume of deionized water to obtain a citrus pectin solution of a second target concentration, and the pH value of the citrus pectin solution of the second target concentration is adjusted to 4.5 to obtain a target citrus pectin solution, and calcium chloride of a preset induced mass is added to a preset induced volume of deionized water to obtain a calcium chloride solution of a target induced concentration, and the calcium chloride solution of the target induced concentration is added to the target citrus pectin solution to induce gelation to obtain a pectin solvent, and the chitosan coating is immersed in the pectin solvent and immersed and stirred to obtain a mixture, and the mixture is mixed and centrifuged to obtain composite coated particles, and the second target concentration is set to Ed, Ed=3%, the target induction concentration is set to Eyd, Eyd=5%, and the immersion and stirring time is set to Bqr, Bqr=30min.

[0105] Specifically, the preset dissolution mass refers to the mass of chitosan determined according to demand when preparing the chitosan solvent, for example, the preset dissolution mass is 20g, the preset dissolution volume refers to the volume of the acetic acid solution used in the preparation of the chitosan solvent, for example, the preset dissolution volume is 100ml, the acetic acid solution refers to the solution obtained by mixing acetic acid and water in proportion, the dissolution refers to the process of adding chitosan to the acetic acid solution to disperse the chitosan into a uniform solution, the target concentration refers to the solution concentration desired to be achieved during the preparation process, the preset cross-linking mass refers to the mass of genipin used during the cross-linking treatment, for example, the preset cross-linking mass is 5g, and the genipin is Refers to a natural polysaccharide used to prepare a cross-linked product. The cross-linking treatment refers to the process of mixing a chitosan complex with genipin to cause a chemical reaction between the two to form a cross-linked structure. The centrifugal washing treatment refers to the process of centrifuging the cross-linked product, removing the supernatant, and washing with deionized water. The concentration of the acetic acid solution in the preset dissolution volume refers to the concentration of the acetic acid solution used to dissolve chitosan. The cross-linking treatment temperature refers to the temperature set during the cross-linking reaction. The cross-linking treatment time refers to the time the reaction is maintained during the cross-linking treatment. The preset pectin mass refers to the mass of citrus pectin set according to demand when preparing the citrus pectin solution. For example, the preset pectin mass is 3 0g, the preset second dissolution volume refers to the volume of deionized water used in preparing the citrus pectin solution, for example, the preset second dissolution volume is 500ml, the second target concentration refers to the concentration desired to be achieved in preparing the citrus pectin solution, the pH value of the citrus pectin solution of the second target concentration refers to the pH value desired to be achieved in the process of adjusting the pH value of the citrus pectin solution, the preset induced mass refers to the mass of calcium chloride used in the induced gelation treatment, for example, the preset induced mass is 10g, the calcium chloride refers to an inorganic salt used in the gelation process of food and biological materials, and the preset induced volume refers to the volume of deionized water used in preparing the calcium chloride solution. For example, the preset induction volume is 200 ml, the target induction concentration refers to the concentration desired to be achieved when preparing the calcium chloride solution, the induced gelation treatment refers to the process of adding the calcium chloride solution to the citrus pectin solution, and forming a three-dimensional network structure of the pectin through the reaction, thereby producing a gel, the immersion refers to the method of completely immersing the chitosan coating in the pectin solvent, the immersion stirring refers to the process of stirring the mixture using a stirring device during the immersion process, the mixed centrifugal treatment refers to the process of centrifuging the mixture to remove unreacted components and impurities and separate the composite coated particles, and the immersion stirring time refers to the time duration during the immersion stirring process.

[0106] Specifically, during the coating process in step S4, a double-layer coating process of "chitosan cross-linking-pectin gelation" is used to enhance the activity retention of functional components during storage, processing and digestion, thereby further enhancing the nutritional value and digestibility of the zeolite nano-biofeed complex.

[0107] Specifically, when the coating treatment is performed in real time on step S4, the pH value of the chitosan dissolution process is obtained in real time to obtain a real-time dissolution pH value Prj, and the real-time dissolution pH value Prj is compared with the preset dissolution pH value P0. The effectiveness of the chitosan dissolution is judged according to the comparison result, and the chitosan dissolution process is corrected according to the judgment result, wherein:

[0108] When Prj>P0, the chitosan dissolution is determined to be invalid. The chitosan dissolution process is corrected by adding a first correction volume of acetic acid solution to the preset dissolution volume of acetic acid solution. The preset dissolution volume is set to F1, the first correction volume is set to Fj1, and the concentration of the first correction volume of acetic acid solution is set to Ey1, Ey1=1%, Fj1=5%×F1;

[0109] When Prj = P0, the chitosan dissolution is determined to be effective, and the chitosan dissolution process is not corrected;

[0110] When Prj<P0, the chitosan dissolution is determined to be invalid. The chitosan dissolution process is corrected by adding a second correction volume of sodium hydroxide solution to the preset dissolution volume of acetic acid solution. The preset dissolution volume is set to F1, the second correction volume is set to Fj2, and the concentration of the second correction volume of sodium hydroxide solution is Eq1, Eq1=1%, Fj2=5%×F1;

[0111] When the coating process is monitored in real time in step S4, the film thickness of the composite coated particles is obtained to obtain the composite coated particle film thickness H, and the composite coated particle film thickness H is compared with the preset composite coated particle film thickness H0. The effectiveness of the coating process is judged based on the comparison result, and the coating process is optimized in real time based on the judgment result, wherein:

[0112] When H>H0, the coating treatment is determined to be invalid, and the real-time optimization treatment method of the coating treatment process is to soak the composite coated particles in a weakly acidic aqueous solution for 5 minutes to obtain soaked particles, and optimize the drying treatment of the soaked particles to obtain real-time optimized particles, and obtain the film thickness of the real-time optimized particles. When the film thickness of the real-time optimized particles is reduced to the preset composite coated particle film thickness H0, the real-time optimized particles are output as target coated particles;

[0113] When H=H0, the coating treatment is judged to be effective, and the coating treatment process is not optimized in real time;

[0114] When H<H0, the effectiveness of the coating treatment is determined to be invalid, and the real-time optimization method of the coating treatment process is to perform real-time optimization on the preset dissolution mass and the preset pectin mass, and set the preset dissolution mass after real-time optimization to J1`, and the preset pectin mass after real-time optimization to J2`, the preset dissolution mass is J1, the preset pectin mass is J2, J1`=J1×H0 / H, J2`=J2×H0 / H, and repeat the coating treatment process according to the preset dissolution mass J1` after real-time optimization and the preset pectin mass J2` after real-time optimization.

[0115] Specifically, the pH value in the chitosan dissolution process refers to the acidity and alkalinity in the chitosan dissolution process, the real-time dissolution pH value Prj refers to the acidity and alkalinity in the chitosan dissolution process obtained by real-time monitoring during the chitosan dissolution process, the preset dissolution pH value P0 refers to the ideal pH value preset in the chitosan dissolution process, for example, the preset dissolution pH value P0=5, the first correction volume refers to the volume of acetic acid solution to be added, the concentration of the acetic acid solution of the first correction volume refers to the concentration of the acetic acid solution used to correct the chitosan dissolution process, the second correction volume refers to the volume of sodium hydroxide solution to be added, the sodium hydroxide solution refers to the alkaline solution used in the dissolution process, the concentration of the second correction volume of sodium hydroxide solution refers to the concentration of the sodium hydroxide solution used to correct the chitosan dissolution process, the composite coated particle film thickness H refers to the coating During the treatment process, the thickness of the outer shell of the composite coated particles, the preset composite coated particle film thickness H0 refers to the ideal film thickness pre-set during the coating treatment process, for example, the preset composite coated particle film thickness H0 has a value range of 100nm≤H0≤200nm, the soaking refers to placing the composite coated particles in a weakly acidic aqueous solution, the weakly acidic aqueous solution refers to an aqueous solution with a pH value in the range of 4-6, such as dilute sulfuric acid and acetic acid solution, the soaking time refers to the duration of the composite coated particles soaked in the weakly acidic aqueous solution, the optimized drying treatment refers to the drying treatment of the soaked particles, the real-time optimized particle film thickness refers to the film thickness achieved by the composite coated particles after the coating treatment process is optimized in real time, this embodiment does not limit the method for obtaining the film thickness of the composite coated particles, such as it can be set to obtain the film thickness of the composite coated particles through a spectroscopic reflectometer.

[0116] Specifically, when the coating process is monitored in real time in step S4, the intelligent monitoring system of "pH dynamic correction-film thickness closed-loop control" is used to achieve precise control of the coating process, thereby improving the stability and effectiveness of the zeolite nano-biofeed complex.

[0117] Specifically, when the target coated particles are safety tested in step S5, the residual amount of genipin in the target coated particles is detected by HPLC to obtain a residual amount of genipin N, and the residual amount of genipin N is compared with a preset residual amount of genipin N0. The safety compliance of the target coated particles is judged according to the comparison results, and the target coated particles are output according to the judgment results, wherein;

[0118] When N≥N0, the target coated particles are judged to have failed to meet the safety standards. The target coated particles are output by using an adsorption material to adsorb the target coated particles to obtain treated particles, and safety testing is performed on the treated particles until the safety standards of the treated particles are met.

[0119] When N<N0, the safety compliance of the target coated particles is determined to be met, and the output method of the target coated particles is to pre-freeze the target coating at -40℃ for 4h to obtain a pre-frozen coating, and the pre-frozen coating is post-processed and vacuum-dried to obtain a zeolite nano-biofeed complex. The vacuum degree of the post-processing vacuum drying is set to Chc, the temperature of the post-processing vacuum drying is set to Ahc, and the time of the post-processing vacuum drying is set to Bhc, -0.06MPa≤Chc≤-0.08MPa, Ahc=-50℃, and Bhc=24h.

[0120] Specifically, the HPLC method refers to a method for separating, identifying and quantitatively analyzing chemical substances. Its Chinese name is high-performance liquid chromatography, and its full English name is High-Performance Liquid Chromatography. The genipin residue N refers to the residual concentration of genipin in the target coated particles measured by the HPLC method. The preset genipin residue N0 refers to the maximum allowable value of genipin residue set in the safety test, for example, the preset genipin residue N0 = 0.01%. The adsorption material refers to a material used to adsorb and remove substances such as genipin, such as activated carbon and silica gel. The pre-freezing refers to the process of pre-freezing the target coated particles. The post-processing vacuum drying refers to the process of drying the pre-frozen coating under a vacuum environment. The vacuum degree of the post-processing vacuum drying refers to the vacuum pressure maintained during the post-processing vacuum drying process. The post-processing vacuum drying temperature refers to the temperature set when performing post-processing vacuum drying. The post-processing vacuum drying time refers to the time lasted during the post-processing vacuum drying process.

[0121] Specifically, when the target coated particles are safety tested in step S5, the quality of the zeolite nano-biofeed complex is guaranteed through the process of "testing-adsorption-retesting-drying", thereby further improving the stability and effectiveness of the zeolite nano-biofeed complex.

[0122] Specifically, the preparation method of the zeolite nano-biofeed compound of this embodiment is implemented as follows:

[0123] Example 1:

[0124] The formula of embodiment 1 is as follows:

[0125] 70 parts by mass of zeolite;

[0126] 10 parts by mass of lactic acid bacteria dry powder;

[0127] 10 parts by mass of an amylase product;

[0128] 10 parts by mass of cellulose;

[0129] 2 parts by mass of chitosan;

[0130] 3 parts by mass of citrus pectin.

[0131] The preparation method of Example 1:

[0132] Step S1, measuring the specific surface area of ​​the zeolite to obtain the specific surface area S of the zeolite, comparing the specific surface area S of the zeolite with the preset specific surface area S0, judging whether the specific surface area of ​​the zeolite meets the standard based on the comparison result, and outputting the zeolite based on the judgment result, wherein:

[0133] When S≥S0, the zeolite specific surface area is determined to be up to standard, and the zeolite is output as a zeolite with a specific surface area that meets the standard. The preset particle size d0 is calculated and set to d0=6 / (S×ρ), where ρ is the density of the zeolite.

[0134] When S<S0, it is determined that the specific surface area of ​​the zeolite does not meet the standard, and the zeolite is output as a zeolite with a specific surface area that does not meet the standard;

[0135] Step S2, adding the zeolite with a qualified specific surface area to a cleaner for cleaning to obtain a cleaned zeolite, adding the cleaned zeolite to a crusher for preliminary crushing to a first particle size to obtain a first zeolite, adding the first zeolite to a planetary ball mill for ball milling to obtain a ball-milled zeolite, setting the first particle size to D1, the grinding medium of the planetary ball mill to Yj, the ball-to-material ratio of the ball milling to Q, the ball milling speed of the planetary ball mill to Vq, 100 mesh ≤ D1 ≤ 200 mesh, Yj is an agate ball, Q = 5:1, 200 r / min ≤ Vq ≤ 600 r / min;

[0136] Step S3, obtaining the actual particle size d of the ball-milled zeolite, comparing the actual particle size d of the ball-milled zeolite with the preset particle size d0, judging whether the actual particle size d of the ball-milled zeolite meets the standard based on the comparison result, and outputting the ball-milled zeolite based on the judgment result, wherein:

[0137] When d≤d0, it is determined that the actual particle size d of the ball-milled zeolite meets the standard, and the ball-milled zeolite is output as nano zeolite;

[0138] When d>d0, it is determined that the actual particle size d of the ball-milled zeolite does not meet the standard, and the ball-milled zeolite is re-added to the planetary ball mill for additional ball milling until the actual particle size d of the ball-milled zeolite meets the standard;

[0139] Step S4, performing a silicon-aluminum ratio test on the zeolite with a non-standard specific surface area by X-ray fluorescence spectroscopy to obtain a silicon-aluminum ratio G of the zeolite with a non-standard specific surface area, comparing the silicon-aluminum ratio G of the zeolite with a preset silicon-aluminum ratio G0 of the zeolite, judging whether the silicon-aluminum ratio of the zeolite with a non-standard specific surface area meets the standard based on the comparison result, and optimizing the zeolite with a non-standard specific surface area based on the judgment result, wherein:

[0140] When G≥G0, the silicon-aluminum ratio of the zeolite with a specific surface area that does not meet the standard is determined to meet the standard, and the optimization treatment of the zeolite with a specific surface area that does not meet the standard is to recycle the zeolite with a specific surface area that does not meet the standard;

[0141] When G<G0, the silicon-to-aluminum ratio of the zeolite with a non-standard specific surface area is determined to be non-standard, and an optimization method for treating the zeolite with a non-standard specific surface area is to steam the zeolite with a non-standard specific surface area to obtain a steam zeolite, and determine whether the specific surface area of ​​the steam zeolite meets the standard;

[0142] Step S5, obtaining the non-framework aluminum content T of the zeolite with a non-standard specific surface area, comparing the non-framework aluminum content T of the zeolite with a non-standard specific surface area with a preset non-framework aluminum content T0, judging the effectiveness of the silicon-to-aluminum ratio G of the zeolite with a non-standard specific surface area according to the comparison result, and adjusting the judgment result of the compliance of the silicon-to-aluminum ratio of the zeolite with a non-standard specific surface area according to the judgment result, wherein:

[0143] When T≤T0, the effective case of the silicon-aluminum ratio G of the zeolite with a specific surface area that does not meet the standard is determined to be effective, and the judgment result of the silicon-aluminum ratio of the zeolite with a specific surface area that does not meet the standard is not adjusted;

[0144] When T>T0, the validity of the silicon-aluminum ratio G of the zeolite whose specific surface area does not meet the standard is determined to be invalid, and the judgment result of the silicon-aluminum ratio compliance of the zeolite whose specific surface area does not meet the standard is adjusted to the judgment that the silicon-aluminum ratio compliance of the zeolite whose specific surface area does not meet the standard is not met;

[0145] The step S6 comprises collecting a sample strain from the intestinal environment of the animal, isolating a target strain from the sample strain by a plate streaking method, performing physiological and biochemical identification and molecular biological identification on the target strain to obtain lactic acid bacteria, adding the lactic acid bacteria to an MRS medium for expansion culture to obtain a lactic acid bacteria fermentation broth, and separating the lactic acid bacteria cells in the lactic acid bacteria fermentation broth by a cell centrifugation method to obtain lactic acid bacteria cells, concentrating the lactic acid bacteria cells to obtain concentrated cells, and drying the concentrated cells by a freeze-drying method to obtain lactic acid bacteria dry powder, setting the expansion culture temperature to A, 30° C. ≤ A ≤ 42° C., and the oxygen condition to anaerobic conditions;

[0146] Step S7, screening Bacillus and Aspergillus by enzyme activity assay, selecting Bacillus and Aspergillus with enzyme activities meeting preset enzyme activities as production strains, inoculating the production strains into liquid culture medium for fermentation culture to obtain enzyme fermentation broth, removing enzyme bacteria and impurities in the enzyme fermentation broth by enzyme centrifugation to obtain a crude enzyme liquid, and purifying the crude enzyme liquid to obtain an amylase product, setting the fermentation culture temperature to Af, 30°C ≤ Af ≤ 37°C, and the fermentation culture pH value to P, 6 ≤ P ≤ 7;

[0147] Step S8, adding nano zeolite to deionized water to obtain a deionized liquid, placing the deionized liquid in a magnetic stirrer for magnetic stirring to obtain a suspension, placing the suspension in a high-speed stirrer for high-speed stirring to obtain a zeolite dispersion, adding lactic acid bacteria dry powder, amylase product and cellulose to the zeolite dispersion, and using a high-speed stirrer for composite stirring to obtain a complex solution, placing the complex solution in a centrifuge for centrifugation, and removing the supernatant to obtain a composite precipitate, washing the composite precipitate, and repeating the centrifugation until the washing process is repeated 3 times to obtain a zeolite biocomposite, and vacuum drying the zeolite biocomposite to obtain composite particles, wherein:

[0148] The speed of magnetic stirring is Vc, the time of magnetic stirring is Bc, 200r / min≤Vc≤500r / min, 10min≤Bc≤15min;

[0149] The speed of high-speed stirring is Vg, the time of high-speed stirring is Bg, 1000r / min≤Vg≤5000r / min, 1h≤Bg≤2h;

[0150] The speed of compound stirring is Vf, the time of compound stirring is Bf, 800r / min≤Vf≤3000r / min, 2h≤Bf≤4h;

[0151] The speed of centrifugal treatment is Vx, the time of centrifugal treatment is Bx, 3000r / min≤Vf≤8000r / min, 10min≤Bf≤15min;

[0152] The vacuum degree of vacuum drying treatment is Cz, the temperature of vacuum drying treatment is Az, -0.08MPa≤Bf≤-0.1MPa, 30℃≤Az≤60℃;

[0153] Step S9, adding a preset dissolution mass of chitosan to a preset dissolution volume of acetic acid solution for dissolution to obtain a chitosan solvent of a target concentration, adding the composite particles to the chitosan solvent of the target concentration to obtain a chitosan composite, adding a preset cross-linking mass of genipin to the chitosan composite for cross-linking treatment to obtain a cross-linked product, and centrifuging and washing the cross-linked product to obtain a chitosan coating, setting the concentration of the preset dissolution volume of acetic acid solution to Ey, Ey=1%, the target concentration to Em, Em=2%, the cross-linking treatment temperature to Ajl, Ajl=50°C, and the cross-linking treatment time to Bjl, Bjl=1h;

[0154] Step S10, further adding citrus pectin of a preset pectin mass to a preset second dissolution volume of deionized water to obtain a citrus pectin solution of a second target concentration, and adjusting the pH value of the citrus pectin solution of the second target concentration to 4.5 to obtain a target citrus pectin solution, adding a preset induced mass of calcium chloride to a preset induced volume of deionized water to obtain a calcium chloride solution of a target induced concentration, adding the calcium chloride solution of the target induced concentration to the target citrus pectin solution to induce gelation to obtain a pectin solvent, immersing the chitosan coating in the pectin solvent, and immersing and stirring to obtain a mixture, mixing and centrifuging the mixture to obtain composite coated particles, setting the second target concentration to Ed, Ed = 3%, the target induction concentration to Eyd, Eyd = 5%, and the immersion and stirring time to Bqr, Bqr = 30 min;

[0155] Step S11, obtaining the pH value of the chitosan dissolution process in real time to obtain a real-time dissolution pH value Prj, comparing the real-time dissolution pH value Prj with the preset dissolution pH value P0, judging the effectiveness of chitosan dissolution based on the comparison result, and correcting the chitosan dissolution process based on the judgment result, wherein:

[0156] When Prj>P0, the chitosan dissolution is determined to be invalid. The chitosan dissolution process is corrected by adding a first correction volume of acetic acid solution to the preset dissolution volume of acetic acid solution. The preset dissolution volume is set to F1, the first correction volume is set to Fj1, and the concentration of the first correction volume of acetic acid solution is set to Ey1, Ey1=1%, Fj1=5%×F1;

[0157] When Prj = P0, the chitosan dissolution is determined to be effective, and the chitosan dissolution process is not corrected;

[0158] When Prj<P0, the chitosan dissolution is determined to be invalid. The chitosan dissolution process is corrected by adding a second correction volume of sodium hydroxide solution to the preset dissolution volume of acetic acid solution. The preset dissolution volume is set to F1, the second correction volume is set to Fj2, and the concentration of the second correction volume of sodium hydroxide solution is Eq1, Eq1=1%, Fj2=5%×F1;

[0159] Step S12, obtaining the film thickness of the composite coated particles to obtain the composite coated particle film thickness H, comparing the composite coated particle film thickness H with the preset composite coated particle film thickness H0, judging the effectiveness of the coating process based on the comparison result, and optimizing the coating process in real time based on the judgment result, wherein:

[0160] When H>H0, the coating treatment is determined to be invalid, and the real-time optimization treatment method of the coating treatment process is to soak the composite coated particles in a weakly acidic aqueous solution for 5 minutes to obtain soaked particles, and optimize the drying treatment of the soaked particles to obtain real-time optimized particles, and obtain the film thickness of the real-time optimized particles. When the film thickness of the real-time optimized particles is reduced to the preset composite coated particle film thickness H0, the real-time optimized particles are output as target coated particles;

[0161] When H=H0, the coating treatment is judged to be effective, and the coating treatment process is not optimized in real time;

[0162] When H<H0, the coating treatment is determined to be invalid, and the real-time optimization method of the coating treatment process is to optimize the preset dissolution mass and the preset pectin mass in real time, setting the preset dissolution mass after real-time optimization to J1', the preset pectin mass after real-time optimization to J2', the preset dissolution mass to J1, the preset pectin mass to J2, J1'=J1×H0 / H, J2'=J2×H0 / H, and repeating the coating treatment process according to the preset dissolution mass after real-time optimization J1' and the preset pectin mass after real-time optimization J2';

[0163] Step S13, detecting the residual amount of genipin in the target coated particles by HPLC method to obtain the residual amount of genipin N, comparing the residual amount of genipin N with the preset residual amount of genipin N0, judging the safety compliance of the target coated particles according to the comparison results, and outputting the target coated particles according to the judgment results, wherein;

[0164] When N≥N0, the target coated particles are judged to have failed to meet the safety standards. The target coated particles are output by using an adsorption material to adsorb the target coated particles to obtain treated particles, and safety testing is performed on the treated particles until the safety standards of the treated particles are met.

[0165] When N<N0, the safety compliance of the target coated particles is determined to be met, and the output method of the target coated particles is to pre-freeze the target coating at -40℃ for 4h to obtain a pre-frozen coating, and the pre-frozen coating is post-processed and vacuum-dried to obtain a zeolite nano-biofeed complex. The vacuum degree of the post-processing vacuum drying is set to Chc, the temperature of the post-processing vacuum drying is set to Ahc, and the time of the post-processing vacuum drying is set to Bhc, -0.06MPa≤Chc≤-0.08MPa, Ahc=-50℃, and Bhc=24h.

[0166] Example 2:

[0167] The formula of embodiment 2 is as follows:

[0168] 47 parts by mass of zeolite;

[0169] 7 parts by mass of lactic acid bacteria dry powder;

[0170] 7 parts by weight of an amylase preparation;

[0171] 7 parts by weight of cellulose;

[0172] 1.4 parts by mass of chitosan;

[0173] 2 parts by mass of citrus pectin.

[0174] The preparation method of embodiment 2:

[0175] The preparation method of Example 2 is consistent with the preparation method of Example 1.

[0176] Example 3:

[0177] The formula of embodiment 1 is as follows:

[0178] 93 parts by mass of zeolite;

[0179] 13 parts by weight of lactic acid bacteria dry powder;

[0180] 13 parts by weight of an amylase preparation;

[0181] 13 parts by weight of cellulose;

[0182] 2.5 parts by mass of chitosan;

[0183] 4 parts by mass of citrus pectin.

[0184] The preparation method of Example 3:

[0185] The preparation method of Example 3 is consistent with the preparation method of Example 1.

[0186] Example 4:

[0187] The formula of embodiment 4 is as follows:

[0188] 5 parts by mass of nano zeolite;

[0189] 2 parts by weight of Lactobacillus;

[0190] The mass parts are 93 parts of corn flour.

[0191] The preparation method of embodiment 4:

[0192] Step S1, mixing nano zeolite and lactobacillus uniformly to obtain a first mixture;

[0193] Step S2, adding corn flour to the first mixture and mixing to obtain a composite;

[0194] Step S3, drying the complex at 50° C. to obtain a zeolite probiotic complex, with the drying time being 3 hours.

[0195] Example 5:

[0196] The formula of embodiment 5 is as follows:

[0197] 60 parts by mass of nano zeolite;

[0198] 20 parts by weight of cellulase;

[0199] 20 parts by mass of amylase;

[0200] The preparation method of embodiment 5:

[0201] Preparation method:

[0202] Step S1, mixing nano zeolite with cellulase and amylase to obtain a complex;

[0203] Step S2: drying the complex at 40° C. to obtain a zeolite-enzyme preparation complex. The drying time is 4 hours.

[0204] Specifically, the test experiments were conducted on Examples 1-5, and the experimental data are shown in the following table:

[0205] Experimental Project Example 1 Example 2 Example 3 Example 4 Example 5 Animal food intake (g / day) 150 140 160 130 145 Growth rate (%) 18 12 15 10 14 Fertilizer conversion rate (%) 75 65 70 60 68 Survival rate (%) 96 92 95 90 93 Nutrient digestibility (%) 82 75 80 70 78 Immune indicators 250 230 260 210 240 side effect 1 1 1 2 1

[0206] Among them, animal feed intake is tested according to ISO 6496:1999 standard, growth rate is tested according to AGIDE 201 standard, fertilizer conversion rate is tested according to NRC Feed Efficiency Assessment Guidelines standard, survival rate is tested according to ANZCCART standard, nutrient digestibility is tested according to GB / T 23742-2009 standard, immune indicators are tested according to ELISA standard, and side effects are tested according to ECHA toxicity scoring standard.

[0207] Specifically, the experimental data show that Example 1 is superior to Examples 2, 3, 4, and 5 in terms of animal feed intake, growth rate, fertilizer conversion rate, survival rate, and nutrient digestibility, and is second only to Example 3 in terms of immune indicators. Therefore, Example 1 can improve the digestibility of biological feed and the stability and effectiveness of the zeolite nano-biofeed complex, while reducing the degree of environmental pollution caused by aquaculture waste. In summary, the optimal formula of the zeolite nano-biofeed complex and its preparation method are obtained.

[0208] Thus far, the technical solutions of the present invention have been described in conjunction with the preferred embodiments shown in the accompanying drawings. However, it will be readily understood by those skilled in the art that the scope of protection of the present invention is obviously not limited to these specific embodiments. Without departing from the principles of the present invention, those skilled in the art may make equivalent changes or substitutions to the relevant technical features, and the technical solutions after such changes or substitutions will fall within the scope of protection of the present invention.

Claims

1. A zeolite nano-biofeed compound, characterized in that: The raw materials for preparing the zeolite nano-biofeed compound include: zeolite, lactic acid bacteria dry powder, amylase product, cellulose, chitosan and citrus pectin, wherein: The mass of the zeolite is M1, and M1 is set as the first preset mass, M1=70 parts; The mass of the lactic acid bacteria dry powder is M2, and M2 is set as the second preset mass, M2=10 parts; The mass of the amylase product is M3, and M3 is set as the third preset mass, M3=10 parts; The mass of the cellulose is M4, and M4 is set to be the fourth preset mass, M4=10 parts; The mass fraction of the chitosan is M5, and M5 is set as the fifth preset mass fraction, M5=2 parts; The mass fraction of the citrus pectin is M6, and M6 is set as the sixth preset mass fraction, M6=3 parts.

2. A method for preparing the zeolite nano-biofeed composite according to claim 1, characterized in that: The preparation method comprises: Step S1, crushing the zeolite and monitoring the crushing process in real time to obtain nano zeolite; Step S2, preparing lactic acid bacteria dry powder and amylase product to obtain lactic acid bacteria dry powder and amylase product; Step S3, compounding the nano-zeolite, the lactic acid bacteria powder, the amylase product and the cellulose to obtain composite particles; Step S4, coating the composite particles, chitosan, and citrus pectin, and monitoring the coating process in real time to obtain target coated particles; Step S5: Perform safety testing on the target coated particles to obtain zeolite nano-biofeed complex.

3. The method for preparing the zeolite nano-biofeed compound according to claim 2, characterized in that: When the zeolite is crushed in step S1, the specific surface area of ​​the zeolite is measured to obtain the specific surface area S of the zeolite, the specific surface area S of the zeolite is compared with the preset specific surface area S0, and the compliance of the specific surface area of ​​the zeolite with the standard is judged according to the comparison result, and the zeolite is output according to the judgment result, wherein: When S≥S0, the zeolite specific surface area is determined to meet the standard, and the zeolite is output as a zeolite with a standard specific surface area, and the preset particle size d0 is calculated and set to d0=6 / (S×ρ), where ρ is the zeolite density; When S<S0, it is determined that the specific surface area of ​​the zeolite does not meet the standard, and the zeolite is output as a zeolite with a specific surface area that does not meet the standard; In the step S1, when the zeolite is crushed, the zeolite with a qualified specific surface area is added to a cleaner for cleaning to obtain a cleaned zeolite, and the cleaned zeolite is added to a crusher for preliminary crushing to a first particle size to obtain a first zeolite, and the first zeolite is added to a planetary ball mill for ball milling to obtain a ball-milled zeolite, wherein the first particle size is set to D1, the grinding medium of the planetary ball mill is Yj, the ball-to-material ratio of the ball milling is Q, the ball milling speed of the planetary ball mill is Vq, 100 mesh ≤ D1 ≤ 200 mesh, Yj is an agate ball, Q = 5:1, 200 r / min ≤ Vq ≤ 600 r / min; When the zeolite is crushed in step S1, the actual particle size d of the ball-milled zeolite is also obtained, and the actual particle size d of the ball-milled zeolite is compared with the preset particle size d0. According to the comparison result, whether the actual particle size d of the ball-milled zeolite meets the standard is judged, and the ball-milled zeolite is output according to the judgment result, wherein: When d≤d0, it is determined that the actual particle size d of the ball-milled zeolite meets the standard, and the ball-milled zeolite is output as nano zeolite; When d>d0, it is determined that the actual particle size d of the ball-milled zeolite does not meet the standard, and the ball-milled zeolite is added back into the planetary ball mill for additional ball milling until the actual particle size d of the ball-milled zeolite meets the standard.

4. The method for preparing the zeolite nano-biofeed compound according to claim 2, characterized in that: When the pulverization process is performed in real time on the step S1, the silicon-aluminum ratio of the zeolite with a non-standard specific surface area is detected by X-ray fluorescence spectroscopy to obtain the silicon-aluminum ratio G of the zeolite with a non-standard specific surface area, the silicon-aluminum ratio G of the zeolite with a non-standard specific surface area is compared with the preset silicon-aluminum ratio G0 of the zeolite, and the compliance of the silicon-aluminum ratio of the zeolite with the non-standard specific surface area is judged according to the comparison result, and the zeolite with the non-standard specific surface area is optimized according to the judgment result, wherein: When G≥G0, the silicon-aluminum ratio of the zeolite with a specific surface area that does not meet the standard is determined to meet the standard, and the optimization treatment of the zeolite with a specific surface area that does not meet the standard is to recycle the zeolite with a specific surface area that does not meet the standard; When G<G0, it is determined that the silicon-to-aluminum ratio of the zeolite whose specific surface area does not meet the standard does not meet the standard. The optimization treatment method for the zeolite whose specific surface area does not meet the standard is to steam the zeolite whose specific surface area does not meet the standard to obtain steam zeolite, and judge whether the specific surface area of ​​the steam zeolite meets the standard.

5. The method for preparing the zeolite nano-biofeed compound according to claim 4, characterized in that: When the step S1 performs real-time crushing monitoring on the crushing process, the non-framework aluminum content T of the zeolite with a non-standard specific surface area is also obtained, and the non-framework aluminum content T of the zeolite with a non-standard specific surface area is compared with a preset non-framework aluminum content T0. The effectiveness of the silicon-to-aluminum ratio G of the zeolite with a non-standard specific surface area is judged according to the comparison result, and the judgment result of the compliance of the silicon-to-aluminum ratio of the zeolite with a non-standard specific surface area is adjusted according to the judgment result, wherein: When T≤T0, the effective case of the silicon-aluminum ratio G of the zeolite with a specific surface area that does not meet the standard is determined to be effective, and the judgment result of the silicon-aluminum ratio of the zeolite with a specific surface area that does not meet the standard is not adjusted; When T>T0, the effective situation of judging the silicon-aluminum ratio G of the zeolite whose specific surface area does not meet the standard is invalid, and the judgment result of whether the silicon-aluminum ratio of the zeolite whose specific surface area does not meet the standard meets the standard is adjusted to judging that the silicon-aluminum ratio of the zeolite whose specific surface area does not meet the standard meets the standard is not up to standard.

6. The method for preparing the zeolite nano-biofeed compound according to claim 2, characterized in that: When preparing the lactic acid bacteria dry powder in step S2, sample strains are collected from the intestinal environment of an animal, and a target strain is separated from the sample strain by a plate streaking method, the target strain is subjected to physiological and biochemical identification and molecular biological identification to obtain lactic acid bacteria, the lactic acid bacteria are added to an MRS culture medium for expansion culture to obtain a lactic acid bacteria fermentation broth, and the lactic acid bacteria cells in the lactic acid bacteria fermentation broth are separated by a cell centrifugation method to obtain lactic acid bacteria cells, the lactic acid bacteria cells are concentrated to obtain concentrated cells, and the concentrated cells are dried by a freeze-drying method to obtain lactic acid bacteria dry powder, the expansion culture temperature is set to A, 30°C≤A≤42°C, and the oxygen condition is anaerobic condition; When preparing the amylase product in step S2, Bacillus and Aspergillus are screened by an enzyme activity assay, and Bacillus and Aspergillus with enzyme activities that meet preset enzyme activities are used as production strains, and the production strains are inoculated into a liquid culture medium for fermentation culture to obtain an enzyme fermentation liquid, and the enzyme cells and impurities in the enzyme fermentation liquid are removed by enzyme centrifugation to obtain a crude enzyme liquid, and the crude enzyme liquid is purified to obtain the amylase product, and the fermentation culture temperature is set to Af, 30°C≤Af≤37°C, and the fermentation culture pH value is set to P, 6≤P≤7.

7. The method for preparing the zeolite nano-biofeed compound according to claim 2, characterized in that: In step S3, when performing the composite treatment, nano zeolite is added to deionized water to obtain a deionized liquid, and the deionized liquid is placed in a magnetic stirrer for magnetic stirring to obtain a suspension, and the suspension is placed in a high-speed stirrer for high-speed stirring to obtain a zeolite dispersion, and lactic acid bacteria dry powder, amylase product and cellulose are added to the zeolite dispersion, and composite stirring is performed using a high-speed stirrer to obtain a composite solution, and the composite solution is placed in a centrifuge for centrifugal treatment, and the supernatant is removed to obtain a composite precipitate, and the composite precipitate is washed, and the centrifugal treatment is repeated until the washing treatment is repeated 3 times to obtain a zeolite biocomposite, and the zeolite biocomposite is vacuum dried to obtain composite particles, wherein: The speed of magnetic stirring is Vc, the time of magnetic stirring is Bc, 200r / min≤Vc≤500r / min, 10min≤Bc≤15min; The speed of high-speed stirring is Vg, the time of high-speed stirring is Bg, 1000r / min≤Vg≤5000r / min, 1h≤Bg≤2h; The speed of compound stirring is Vf, the time of compound stirring is Bf, 800r / min≤Vf≤3000r / min, 2h≤Bf≤4h; The speed of centrifugal treatment is Vx, the time of centrifugal treatment is Bx, 3000r / min≤Vf≤8000r / min, 10min≤Bf≤15min; The vacuum degree of the vacuum drying process is Cz, the temperature of the vacuum drying process is Az, -0.08MPa≤Bf≤-0.1MPa, 30℃≤Az≤60℃.

8. The method for preparing the zeolite nano-biofeed compound according to claim 2, characterized in that: In step S4, when performing the coating treatment, chitosan of a preset dissolution mass is added to an acetic acid solution of a preset dissolution volume for dissolution to obtain a chitosan solvent of a target concentration, and the composite particles are added to the chitosan solvent of the target concentration to obtain a chitosan composite agent, genipin of a preset cross-linking mass is added to the chitosan composite agent for cross-linking treatment to obtain a cross-linked product, and the cross-linked product is centrifuged and washed to obtain a chitosan coating, and the concentration of the acetic acid solution of the preset dissolution volume is set to Ey, Ey=1%, the target concentration is set to Em, Em=2%, the cross-linking treatment temperature is set to Ajl, Ajl=50° C., and the cross-linking treatment time is set to Bjl, Bjl=1h; During the coating treatment in step S4, citrus pectin of a preset pectin mass is added to a preset second dissolution volume of deionized water to obtain a citrus pectin solution of a second target concentration, and the pH value of the citrus pectin solution of the second target concentration is adjusted to 4.5 to obtain a target citrus pectin solution, and calcium chloride of a preset induced mass is added to a preset induced volume of deionized water to obtain a calcium chloride solution of a target induced concentration, and the calcium chloride solution of the target induced concentration is added to the target citrus pectin solution to induce gelation to obtain a pectin solvent, and the chitosan coating is immersed in the pectin solvent and immersed and stirred to obtain a mixture, and the mixture is mixed and centrifuged to obtain composite coated particles, and the second target concentration is set to Ed, Ed=3%, the target induction concentration is set to Eyd, Eyd=5%, and the immersion and stirring time is set to Bqr, Bqr=30min.

9. The method for preparing the zeolite nano-biofeed compound according to claim 2, characterized in that: When the coating process is monitored in real time in step S4, the pH value of the chitosan dissolution process is obtained in real time to obtain a real-time dissolution pH value Prj, and the real-time dissolution pH value Prj is compared with a preset dissolution pH value P0. The effectiveness of the chitosan dissolution is judged according to the comparison result, and the chitosan dissolution process is corrected according to the judgment result, wherein: When Prj>P0, the chitosan dissolution is determined to be invalid. The chitosan dissolution process is corrected by adding a first correction volume of acetic acid solution to the preset dissolution volume of acetic acid solution. The preset dissolution volume is set to F1, the first correction volume is set to Fj1, and the concentration of the first correction volume of acetic acid solution is set to Ey1, Ey1=1%, Fj1=5%×F1; When Prj = P0, the chitosan dissolution is determined to be effective, and the chitosan dissolution process is not corrected; When Prj<P0, the chitosan dissolution is determined to be invalid. The chitosan dissolution process is corrected by adding a second correction volume of sodium hydroxide solution to the preset dissolution volume of acetic acid solution. The preset dissolution volume is set to F1, the second correction volume is set to Fj2, and the concentration of the second correction volume of sodium hydroxide solution is Eq1, Eq1=1%, Fj2=5%×F1; When the coating process is monitored in real time in step S4, the film thickness of the composite coated particles is obtained to obtain the composite coated particle film thickness H, and the composite coated particle film thickness H is compared with the preset composite coated particle film thickness H0. The effectiveness of the coating process is judged based on the comparison result, and the coating process is optimized in real time based on the judgment result, wherein: When H>H0, the coating treatment is determined to be invalid, and the real-time optimization treatment method of the coating treatment process is to soak the composite coated particles in a weakly acidic aqueous solution for 5 minutes to obtain soaked particles, and optimize the drying treatment of the soaked particles to obtain real-time optimized particles, and obtain the film thickness of the real-time optimized particles. When the film thickness of the real-time optimized particles is reduced to the preset composite coated particle film thickness H0, the real-time optimized particles are output as target coated particles; When H=H0, the coating treatment is judged to be effective, and the coating treatment process is not optimized in real time; When H<H0, the effectiveness of the coating treatment is determined to be invalid, and the real-time optimization method of the coating treatment process is to perform real-time optimization on the preset dissolution mass and the preset pectin mass, and set the preset dissolution mass after real-time optimization to J1`, and the preset pectin mass after real-time optimization to J2`, the preset dissolution mass is J1, the preset pectin mass is J2, J1`=J1×H0 / H, J2`=J2×H0 / H, and repeat the coating treatment process according to the preset dissolution mass J1` after real-time optimization and the preset pectin mass J2` after real-time optimization.

10. The method for preparing the zeolite nano-biofeed compound according to claim 2, characterized in that: When the step S5 performs safety testing on the target coated particles, the residual amount of genipin in the target coated particles is detected by HPLC method to obtain the residual amount of genipin N, the residual amount of genipin N is compared with the preset residual amount of genipin N0, and the safety compliance of the target coated particles is judged according to the comparison result, and the target coated particles are output according to the judgment result, wherein; When N≥N0, the target coated particles are judged to have failed to meet the safety standards. The target coated particles are output by using an adsorption material to adsorb the target coated particles to obtain treated particles, and safety testing is performed on the treated particles until the safety standards of the treated particles are met. When N<N0, the safety compliance of the target coated particles is determined to be met, and the output method of the target coated particles is to pre-freeze the target coating at -40℃ for 4h to obtain a pre-frozen coating, and the pre-frozen coating is post-processed and vacuum-dried to obtain a zeolite nano-biofeed complex. The vacuum degree of the post-processing vacuum drying is set to Chc, the temperature of the post-processing vacuum drying is set to Ahc, and the time of the post-processing vacuum drying is set to Bhc, -0.06MPa≤Chc≤-0.08MPa, Ahc=-50℃, and Bhc=24h.

Citation Information

Patent Citations

  • Preparation and application of novel bioactive peptide compound feed additive

    CN118177288A

  • Feed additive for ruminants as well as preparation method and application of feed additive

    CN112314797A